A case of salivary duct carcinoma possibly arising from pleomorphic adenoma - Dedy Ariwansa; Durga Paudel; Tetsuro Morikawa; Koki Yoshida; Ariuntsetseg Khurelchuluun; Shuhei Takahashi; Jun Sato; Eiji Nakayama; Hiroki Nagayasu; Yoshihiro Akbiko (Journal of Dentomaxillofacial Science, 2022)
Objective: We report a rare case of salivary duct carcinoma possibly arising from the malignant component of carcinoma ex pleomorphic adenoma. Methods: A 56-year-old Japanese male complained of swelling in the left side of jaw for 2 years which was painless until 2 days ago. On extraoral examination, the face was bilaterally asymmetrical. An ultrasonography revealed hypoechoic mass of size 1.5x2.5x2.5 cm on left parotid gland. Computed tomography (CT) revealed a slight irregular mass on left parotid gland with no infiltration to adjacent tissues. Based on these findings, a clinical diagnosis of left parotid benign tumor was made. Results: A surgical excision was performed under general anesthesia. On histopathological examination, the connective tissue was rich in fibrous components and was accompanied by hyaline. Epithelial cells with high atypia proliferating invasively as cords into connective tissue were observed. The intraductal component had Roman-bridge-like architecture with central portion undergoing comedonecrosis. Based on these findings, a final diagnosis of salivary duct carcinoma possibly arising from pleomorphic adenoma was made. p16 hypermethylation is a known phenomenon in oral malignancy. We also checked the methylation status of p16 gene and found high level of methylation in this tumor. Conclusion: We reported a rare case of salivary duct carcinoma possibly arising from pleomorphic adenoma and also demonstrated high methylation level of p16 gene in the tumor.